Study of atomic collisions by charged particles - Pandey, Ashutosh; Saxena, A K; Mishra, Rajeev; Agarwal, Rajeev (International Multidisciplinary Research Journal, 2012)
The Present study of collision processes involving positive ions provides a sensitive test of the approximate method to develop positron and electron scattering and yields useful information about the role of different works in collision dynamics. This study of laser assisted collision process involves an accurate description of the projectile and the target states in the presence of laser field.Â 